Diversity of Weissella confusa in Pozol and Its Carbohydrate Metabolism - Hernández-Oaxaca, Diana; López-Sánchez, Rafael; Lozano, Luis; Wacher-Rodarte, Carmen; Segovia, Lorenzo; López Munguía, Agustín (Frontiers in Microbiology, 2021)
The genus Weissella is composed of a group of Gram-positive bacteria showing facultative anaerobic fermentative metabolism. The strains of this genus have been isolated from various ecological niches, including a wide variety of fermented cereal foods. Considering pozol -- a fermented beverage based on nixtamalized (lime treated) maize --, this study aimed to determine Weissella abundance in pozol samples and their possible role in fermentation. By sequencing the V3-V4 regions of 16S rDNA, we detected the presence of the genus from the beginning of fermentation, reaching its peak relative abundance (3.89 %) at 3 h after fermentation had started. Five Weissella strains previously isolated from pozol and reported as non-amylolytic were evaluated in this work. We question: Which sugars may be metabolizing if they don´t use starch? In order to that, the capacity of this strains to metabolize xylan, xylooligosaccharides, and sucrose as alternative carbon sources, was evaluated. No growth was observed on birch xylan, but growth did occur on xylooligosaccharides and sucrose. Strains WcL17 and WCP-3A were selected for genomic sequencing because of its xylooligosaccharides growth and glycosyltransferase activity, respectively. Genomes of both strains were assembled and recorded, with a total of 2.3 Mb in 30 contigs for WcL17 and 2.2 Mb in 45 contigs for WCP-3a. Both strains were taxonomically assigned to Weissella confusa species. Genomic analyses were performed to evaluate the gene products encoding active carbohydrate enzymes (CAZy). Both strains have the gene content needed to assimilate sucrose, hemicellulose and surprisingly starch and cellulose residues, sugars available in pozol. The results suggest that the secondary enzymatic activities of Weissella confusa give it a wide versatility to participate in fermentative processes of natural products, with heterogeneous carbon sources.